2023
DOI: 10.1037/ccp0000787
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of group psychotherapy for adults with perfectionism: A randomized controlled trial of dynamic-relational therapy versus psychodynamic supportive therapy.

Abstract: Objective: This randomized controlled trial investigated the efficacy of group dynamic-relational therapy (DRT) relative to group psychodynamic supportive therapy (PST) in treating perfectionism and improving psychological functioning. Hypothesis: Psychodynamically informed therapies, particularly DRT, will be efficacious in treating perfectionism and functioning outcomes. Method: Based on a comprehensive conceptualization of perfectionism, 80 community-recruited, highly perfectionistic individuals were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 82 publications
(124 reference statements)
0
16
0
Order By: Relevance
“…Moreover, the average reduction in depressive symptoms, and the percentage of patients who showed clinically significant improvements in depressive symptoms, was significantly larger for patients who received DRT than patients who received PST. Analyses showed significant changes in all perfectionism components and depression from pre-treatment to post treatment and follow up (Hewitt, Kealy, et al, 2022) in both groups.…”
Section: Dynamic-relational Group Psychotherapymentioning
confidence: 90%
See 3 more Smart Citations
“…Moreover, the average reduction in depressive symptoms, and the percentage of patients who showed clinically significant improvements in depressive symptoms, was significantly larger for patients who received DRT than patients who received PST. Analyses showed significant changes in all perfectionism components and depression from pre-treatment to post treatment and follow up (Hewitt, Kealy, et al, 2022) in both groups.…”
Section: Dynamic-relational Group Psychotherapymentioning
confidence: 90%
“…Finally, we have also introduced an intrapersonal or self-relational component of perfectionism that is reflected, in part, by an individual's internal dialogue with the self. We suggested that this involves not only automatic perfectionistic self-statements and thoughts (Flett et al, 1998) but also automatic critical self-recriminations (Hewitt, Kealy, et al, 2022) and concerns over shortfalls and perceived errors (see Frost et al, 1990). Moreover, we have indicated that this component reflects a behavioral element involving neglect of the self in terms of limited self-care and self-denial.…”
Section: Psychodynamic Relational Perspectivementioning
confidence: 92%
See 2 more Smart Citations
“…One possibility is that unlike concerns over mistakes, trait perfectionism dimensions reflect more deeply engrained ways of relating to the self and others that require a greater relational and supportive emphasis to effect meaningful change. In support, Hewitt et al (2023) randomly assigned participants with clinically elevated perfectionism to 12 sessions of dynamic relational therapy for perfectionism (DRT) or 12 sessions of psychodynamic supportive therapy for perfectionism (PST). At posttreatment, 92%, 38%, and 49% of patients in DRT experienced reliable improvements in self-oriented, other-oriented, and socially prescribed perfectionism, and 85%, 61%, and 39% of patients in PST experienced reliable improvements in self-oriented, other-oriented, and socially prescribed perfectionism.…”
Section: Discussionmentioning
confidence: 99%